Synthesis, Modification And Immobilization Of Copper Benzene-1,3,5-Tricarboxylate For The Removal Of Methylene Blue In Wastewater - Siew, Wei Yuan (2020)
A series of green synthesis methods were applied to synthesize [Cu3(BTC)2(H2O)3]n (CuBTC). The established method uses only water as the synthesis solvent and it is able to be carried out at room temperature. By applying the same synthesis system, a second compound, Cu2(OH)(BTC)(H2O)